Strategies used to establish palliative care in rural low- and middle-income countries: an integrative review. Issue 8 (24th June 2020) - Aregay, Atsede; O'Connor, Margaret; Stow, Jill; Ayers, Nicola; Lee, Susan
Abstract: Globally, 40 million people need palliative care; about 69% are people over 60 years of age. The highest proportion (78%) of adults are from low- and middle-income countries (LMICs), where palliative care still developing and is primarily limited to urban areas. This integrative review describes strategies used by LMICs to establish palliative care in rural areas. A rigorous integrative review methodology was utilized using four electronic databases (Ovid MEDLINE, Ovid Emcare, Embase classic+Embase and CINAHL). The search terms were: 'palliative care', 'hospice care', 'end of life care', 'home-based care', 'volunteer', 'rural', 'regional', 'remote' and 'developing countries' identified by the United Nations (UN) as 'Africa', 'Sub-Saharan Africa', 'low-income' and 'middle- income countries'. Thirty papers published in English from 1990 to 2019 were included. Papers were appraised for quality and extracted data subjected to analysis using a public health model (policy, drug availability, education and implementation) as a framework to describe strategies for establishing palliative care in rural areas. The methodological quality of the reviewed papers was low, with 7 of the 30 being simple programme descriptions. Despite the inclusion of palliative care in national health policy in some countries, implementation in the community was often reliant on advocacy and financial support from non-government organizations. Networking to coordinate care and medication availability near-patient homes were essential features of implementation. Training, role play, education and mentorship were strategies used to support health providers and volunteers. Home- and community-based palliative care services for rural LMICs communities may best be delivered using a networked service among health professionals, community volunteers, religious leaders and technology.